PENGARUH DIRECT MARKETING DAN PRODUCT QUALITY TERHADAP MINAT BELI ULANG PADA LIVE STREAMING MARKETING TIKTOK: (Studi pada pengguna aplikasi Tiktok di Kota Medan) - Harita, Helmin Tety Saputri; Siregar, Onan Marakali (Transpublika Publisher, 2022)
The development of increasingly advanced technology has an impact in various fields. One of the impacts that have experienced technological developments is Social Media. There are many business people who use social media as an e-commerce business platform by presenting innovative features and programs to win market competition. To attract interest and build consumer satisfaction, most e-commerce features Live streaming because it can provide buying and selling activities in real time and reduce consumer anxiety about the quality of the products offered. This research is intended to analyze Direct Marketing and Product Quality influence TikTok users repurchase intention at Medan City. Quantitative research with an approach that is associative was the method of investigation that was utilized in this study. The approach of purposive sampling was utilized for the sampling, and there were a total of one hundred respondents employed as samples. The questionnaires that were distributed through google forms in order to collect the primary data for this study were compared to the literature that was studied in order to collect the secondary data. Validity tests, reliability tests, tests based on the classical assumption, multiple linear regression analysis, and hypothesis tests are the methods of data analysis that are utilized here. According to the findings of the study that was carried out, direct marketing has a significant impact on repurchase intention, and the quality of the product also has a significant impact on repurchase intention (Y). As for the variable repurchase intention, Direct Marketing and Product Quality both have an effect at the same time.